Implementation of a Web-Based System as a Promotional and Product Ordering Media at Spacetrip.LTD - Yusuf Hidayat; Moh Mahmud Yunus; Jupron Jupron (STMIK Methodist Binjai, 2026)
The utilization of independent digital platforms has become crucial for the creative industry to avoid dependence on third-party algorithms and to mitigate the risks of manual data management errors. This study aims to implement a website-based e-commerce information system that integrates promotional functions and real-time order automation at Spacetrip Ltd. The system development method employed is the Agile methodology to support design flexibility, encompassing stages that include requirements analysis, design using Unified Modeling Language (UML), implementation, and system testing. The testing results demonstrate that the developed website-based system successfully automates inventory data synchronization and structured order recapitulation. This system is capable of eliminating inventory information asymmetry and accelerating online customer transactions. In conclusion, this study proves that the application of the Agile method in an independent system effectively enhances operational service quality while optimally expanding digital marketing reach. Future recommendations include the development of predictive analysis features for product sales trends